2005
DOI: 10.1309/bfvvu29hcc5rcky5
|View full text |Cite
|
Sign up to set email alerts
|

Test Performance Comparison of Inform HPV and Hybrid Capture 2 High-Risk HPV DNA Tests Using the SurePath Liquid-Based Pap Test as the Collection Method

Abstract: No US Food and Drug Administration-approved method is available to test for human papillomavirus (HPV) DNA in the SurePath liquid-based Papanicolaou (Pap) test (TriPath Care Technologies, Burlington, NC). We compared the performance characteristics of Inform HPV (Ventana Medical Systems, Tucson, AZ) and Hybrid Capture 2 (HC2; Digene, Gaithersburg, MD) using SurePath for collection. The study included samples from 102 women, aged 18 to 60 years, who underwent a SurePath Pap test immediately before colposcopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The NPV was also lower with INFORM HPV (89%) than with HC2 (100%). 10 In our study of 51 women with ASCUS, the sensitivity of the INFORM HPV for predicting CIN 2/3 was 60% (3 of 5), with an NPV of 94.4%. These studies demonstrated lack of sufficient sensitivity and NPV for detecting CIN 2/3 using the INFORM HPV in SurePath specimens.…”
Section: Discussionmentioning
confidence: 57%
“…The NPV was also lower with INFORM HPV (89%) than with HC2 (100%). 10 In our study of 51 women with ASCUS, the sensitivity of the INFORM HPV for predicting CIN 2/3 was 60% (3 of 5), with an NPV of 94.4%. These studies demonstrated lack of sufficient sensitivity and NPV for detecting CIN 2/3 using the INFORM HPV in SurePath specimens.…”
Section: Discussionmentioning
confidence: 57%
“…The distinction between primary glandular pathology and HSIL that involves endocervical glands can be a diagnostic problem 12. In these specimens, groups of abnormal cells tend to round up during processing of fluid material, and they may be mistaken for cells of glandular origin.…”
mentioning
confidence: 99%
“…13 Our results are similar to others' reports of hrHPV HC2 testing on SurePath TM specimens. 11,12,[23][24][25] In published reports of hrHPV HC2 testing using ThinPrepV R specimens, the sensitivity of abnormal cytology ranges from 50% to 100% for predicting CIN 2 and above. 22 Storage duration and temperature are not reported and such a low sensitivity has not been replicated in other studies.…”
Section: Discussionmentioning
confidence: 99%